The Book of Daniel : Poems - Smith, Aaron, 1974- (Book collections on Project MUSE., 2019)
A tour de force, Aaron Smith's fourth collection of poetry, The Book of Daniel, resists the easy satisfactions of Beauty while managing the contemporary entanglements of art, sex, and grief. Part pop-thriller, part queer rage, and part mourning, these poems depict not only the complications of representation in the age of social media but a critique of identity. Taking on subjects as diverse as the literary canon, his mother's incurable cancer diagnosis, gay bashing, celebrity gossip, bigotry, violence on TV, and Alexander McQueen's suicide, Smith proves that the confessional lyric is not dead. In tangents as wild as they are reigned, with his characteristic blend of directness, vulnerability and humor, these poems take on the world as it is, a world we love even as it resists all intimacy.